Dehydration property of Shrimp (Pandalus borealis) undergoing heat-pump drying process - Guochen, Zhang; Arason, Sigurj; Arnason, Sveinn V (International Journal of Agricultural and Biological Engineering, 2010)
Peeled, headed or whole shrimp (Pandalus borealis) was dried in a heat-pump dryer at -2-0